Optimisation of Beetroot Juice Encapsulation by Freeze-Drying - Vesna Tumbas Šaponjac; Jasna Čanadanović-Brunet; Gordana Ćetković; Mirjana Jakišić; Jelena J. Vulić; Slađana Stajčić; Vanja Šeregelj (Polish Journal of Food and Nutrition Sciences)
Sensitivity of natural antioxidants could be improved using encapsulation technologies. In this study, encapsulation of beetroot juice (BJ) with soy proteins has been optimized in terms of the wall:core ratio, BJ dilution and mixing time of both components, maximizing DPPH radical scavenging activity (SA) and the encapsulation efficiency (EE) based on the total phenolics content. Multi response optimization has indicated that the optimal encapsulation is accomplished when soy protein is mixed with undiluted BJ at a wall:core ratio of 50 g/L for 9.8 min. Applying these conditions, the optimal encapsulate has been produced, where the contents of total phenolics, flavonoids and betalains were 150.71 mg GAE/100 g, 9.31 mg RE/100 g, and 521.28 mg/100 g, respectively, while EE and SA were in accordance with the values obtained by optimization, i.e. 92.48% and 1.01 mmol TE/100 g, respectively, confirming the validity of the optimization process. The resulting encapsulates have favorable physicochemical and functional characteristics and can be potentially applied as natural color additives.